2004
DOI: 10.1111/j.1600-0889.2004.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual time-series of total filterable atmospheric mercury concentrations in the Arctic

Abstract: Total atmospheric mercury (TAM) is operationally defined as the sum of gaseous elemental mercury (GEM), gaseous oxidized inorganic mercury (GOIM), which is also called reactive gaseous mercury (RGM), and total filterable mercury (TFM). An annual weekly‐integrated time‐series of TFM concentrations in ambient air at Alert, Nunavut, Canada from March 1998 to March 1999 is reported in this paper. The observed TFM concentrations ranged from 0 to 0.37 ng m−3 with the highest value occurring in the spring after polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…This method has been previously presented in many publications, for example: Munthe et al, 2001;Landis et al, 2002;. Calibration Lu et al, 2001;Steffen et al, 2002;Banic et al, 2003;Slemr et al, 2003;Steffen et al, 2003a;Steffen et al, 2003b;Ariya et al, 2004;Lu and Schroeder, 2004 (Berg et al, 2003a;Berg et al, 2003b;Wangberg et al, 2003;Ferrari et al, 2005;Sprovieri et al, 2005aSprovieri et al, , 2005bFain et al, 2006b;Fain et al, 2006a;Sommar et al, 2007) Resolute GEM Tekran 2537A (Lahoutifard et al, 2005) Station Nord GEM Tekran 2537A Gardis (Ferrari et al, 2004a;Ferrari et al, 2004b;Skov et al, 2004) Neumayer GEM, RGM Tekran 2537A Tekran 2537A /130 (prototype) (Ebinghaus et al, 2002;Temme et al, 2003) Terra Nova GEM, RGM Tekran 2537A/1130 (Sprovieri et al, 2002) North Atlantic Ocean…”
Section: Gaseous Elemental Mercury (Gem)mentioning
confidence: 99%
“…This method has been previously presented in many publications, for example: Munthe et al, 2001;Landis et al, 2002;. Calibration Lu et al, 2001;Steffen et al, 2002;Banic et al, 2003;Slemr et al, 2003;Steffen et al, 2003a;Steffen et al, 2003b;Ariya et al, 2004;Lu and Schroeder, 2004 (Berg et al, 2003a;Berg et al, 2003b;Wangberg et al, 2003;Ferrari et al, 2005;Sprovieri et al, 2005aSprovieri et al, , 2005bFain et al, 2006b;Fain et al, 2006a;Sommar et al, 2007) Resolute GEM Tekran 2537A (Lahoutifard et al, 2005) Station Nord GEM Tekran 2537A Gardis (Ferrari et al, 2004a;Ferrari et al, 2004b;Skov et al, 2004) Neumayer GEM, RGM Tekran 2537A Tekran 2537A /130 (prototype) (Ebinghaus et al, 2002;Temme et al, 2003) Terra Nova GEM, RGM Tekran 2537A/1130 (Sprovieri et al, 2002) North Atlantic Ocean…”
Section: Gaseous Elemental Mercury (Gem)mentioning
confidence: 99%
“…PBM is associated with airborne particles -e.g., dust, soot, sea-salt aerosols or ice crystals -or originates from the adsorption of reactive mercury onto atmospheric particles (Lu and Schroeder, 2004). Field and modeling studies (Rutter and Schauer, 2007;Amos et al, 2012;Steffen et al, 2014) suggested that the partitioning of mercury onto particles might be driven by air temperature and aerosol particle loadings.…”
Section: Particle-bound Mercurymentioning
confidence: 99%
“…Particulate mercury is associated with airborne particles, such as dust, soot, and sea salt aerosols, and is likely produced by adsorption of RGM onto atmospheric particles (Lu and Schroeder, 2004). Most research indicates higher Hg P concentrations and fractions in suspended particles in urban or industrial areas than in rural areas (Fang et al, 2001a(Fang et al, , 2011a(Fang et al, , 2012Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%